Dinamika Kelompok pada Majelis Taklim Jami’atul Muslimah di Desa Mataram Kabupaten Musi Rawas - Putri, Givani Anisa; Hakim, Imron A.; Wati, Evy Ratna Kartika (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan Universitas Negeri Semarang, 2019)
This study aims to determine the knowledge of group dynamics in Majelis Taklim Jami'atul Muslimah at Mataram Village, Tugumulyo Subdistrict, Musi Rawas Regency. This type of research is quantitative research with a descriptive approach. Data collection techniques include primary data and secondary data. The population of this study amounted to 33 people and a sample of 33 people became total sampling. Data were analyzed descriptively using percentages. The results showed that knowledge of group dynamics in Majelis Taklim Jami'atul Muslimah was in the high category with a percentage of 78.8%. Conclusions from this study are that knowledge of group dynamics is in a high category because of clear group goals, group task functions have been carried out well, solidarity between members and good group leaders and a well-formed group atmosphere.